2017
DOI: 10.1111/sms.12911
|View full text |Cite
|
Sign up to set email alerts
|

Unstable rocker shoes promote recovery from marathon‐induced muscle damage in novice runners

Abstract: We recently reported that wearing unstable rocker shoes (Masai Barefoot Technology: MBT) may enhance recovery from marathon race-induced fatigue. However, this earlier study only utilized a questionnaire. In this study, we evaluated MBT utilizing objective physiological measures of recovery from marathon-induced muscle damages. Twenty-five university student novice runners were divided into two groups. After running a full marathon, one group wore MBT shoes (MBT group), and the control group (CON) wore ordinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
(48 reference statements)
2
9
0
1
Order By: Relevance
“…However, marathon races are often reported to induce muscle damage in the lower extremity muscles, manifesting as decreased muscle strength [1][2][3][4], occurrence of delayed onset muscle soreness [4,5], and increased plasma creatine kinase (CK) levels [1,2,4], which usually peak at 1-3 days after the race and take several days to recover. To better understand the location of muscle damage in the leg muscles induced by a marathon, previous studies using ultrasound elastography have demonstrated that the thigh and lower leg muscles became harder after a marathon [6,7], that the amount of change in muscle mechanical properties (e.g., muscle hardness) does not occur uniformly within the lower extremity muscles, and that the recovery time for each muscle varies. Muscle hardness in the vastus lateralis, biceps femoris, and soleus muscles returned to baseline at 8 days after the race, whereas the rectus femoris and gastrocnemius medial muscle hardness did not recover even after 8 days [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, marathon races are often reported to induce muscle damage in the lower extremity muscles, manifesting as decreased muscle strength [1][2][3][4], occurrence of delayed onset muscle soreness [4,5], and increased plasma creatine kinase (CK) levels [1,2,4], which usually peak at 1-3 days after the race and take several days to recover. To better understand the location of muscle damage in the leg muscles induced by a marathon, previous studies using ultrasound elastography have demonstrated that the thigh and lower leg muscles became harder after a marathon [6,7], that the amount of change in muscle mechanical properties (e.g., muscle hardness) does not occur uniformly within the lower extremity muscles, and that the recovery time for each muscle varies. Muscle hardness in the vastus lateralis, biceps femoris, and soleus muscles returned to baseline at 8 days after the race, whereas the rectus femoris and gastrocnemius medial muscle hardness did not recover even after 8 days [6].…”
Section: Introductionmentioning
confidence: 99%
“…For all other items, "yes" was scored 1 and "no" and "unable to determine" were scored 0. Based on the risk of bias assessment scores, studies were classified as very high quality/very low risk of bias (26)(27)(28), good quality/low risk of bias (20)(21)(22)(23)(24)(25), fair quality/fair risk of bias (15)(16)(17)(18)(19) or poor quality/high risk of bias (� 14) [43]. Higher scores indicated less risk of bias than lower scores.…”
Section: Risk Of Bias and Quality Appraisalmentioning
confidence: 99%
“…More recently, Lopéz-Lopéz et al [22] demonstrated an increase in venous return in the feet with shoes equipped with orthotics (i.e., customized with ethylene-vinyl acetate material). However, in addition to these technologies (i.e., foot compression devices, insoles and orthotics) to improve venous function, there are now shoe products (e.g., sandals, heelless shoes) that can improve venous flow [23][24][25] and might optimize recovery [26]. Indeed, athletes are now wearing "recovery" shoes (e.g., flipflops, sandals) between series of exercise and after training session or competition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desde 1999 a 2013, el foco de estudio se centró en el análisis de variables cinemáticas, cinéticas y de actividad eléctrica muscular -a través del uso de la electromiografía (EMG)-que se producían de manera aguda luego de una sesión de entrenamiento a pie descalzo. Debido a que ya se han comprobado varias hipótesis relacionadas con los cambios crónicos de quienes comienzan a practicar BFR, es que se han empezado a estudiar otras variables tales como el control de la estabilidad en el plano frontal (Ekizos, Santuz, & Arampatzis, 2017), cargas sobre el tendón de Aquiles (Rice & Patel, 2017), equilibrio estático en posturografía (Smith et al, 2015), rotación tibial y su influencia en la aducción del calcáneo (Fischer, Willwacher, Hamill, & Bruggemann, 2017), uso de calzado minimalista para la recuperación luego de correr un maratón (Nakagawa et al, 2017), rol que cumple la fatiga en la absorción de fuerzas del tobillo (Hashish, Samarawickrame, Baker, & Salem, 2016), mejora de capacidades cognitivas que se producen por correr descalzos (Alloway, Alloway, Magyari, & Floyd, 2016), rigidez muscular (Tam, Astephen Wilson, Coetzee, van Pletsen, & Tucker, 2016), economía de carrera en mujeres (Berrones et al, 2016), cambio en la tipología del arco plantar longitudinal medial (APLM) (Dolenec, Radi, & Strojnik, 2015), y la inclinación del terreno por donde se corre (An, Rainbow & Cheung, 2015), entre otras.…”
Section: Introductionunclassified